Perception of Price, Accessibility, and Service Perception on Patient Return Visit Interest: Empirical Study from Outpatient Services at Halo Bayi Clinic Limbo, Depok, Indonesia - Putri, Zaskia Respatiningtyas; Nurmawaty, Dwi; Febriyanty, Deasy; Silviana, Intan (Golden Ratio of Data in Summary, 2025)
Revisit interest refers to visitors' intention to return to a place within a specific period and their willingness to revisit the location frequently. A preliminary study conducted on 10 respondents found that 30% of patients had a revisit interest, while 70% were not interested. This study aims to identify the factors associated with revisit interest in outpatient healthcare services at the Halo Bayi Clinic, Limo branch, Depok, in 2024. The study employs a cross-sectional method with a sample size of 100 respondents at the Halo Bayi Clinic, Limo branch. The sampling technique used is purposive sampling, and data analysis includes univariate and bivariate analysis using the chi-square test. The study was conducted from October 2024 to January 2025. The univariate results show that the highest proportion of respondents interested in revisiting was 58 respondents (58%), those who perceived the price as affordable were 62 respondents (62%), those who found the clinic easily accessible were 53 respondents (53%), and those with a positive perception of healthcare providers were 63 respondents (63%). The bivariate analysis results indicate no significant relationship between price perception and revisit interest p-value 0.0139, PR=0.734 and 95% CI = 0.501 - 1.076, and no significant relationship between accessibility and revisit interest p-value 0.053. (PR=0.689 dan 95% CI = 0.482 - 0.984), no significant relationship between perception of healthcare providers and revisit interest, p-value 0.037 (PR=0.649 and 95% CI = 0.431 - 0.976). This can positively impact patient satisfaction, service quality, and efforts to improve public health. Additionally, a high revisit also contributes to increasing patient trust in healthcare facilities, which ultimately supports the effectiveness of health programs and the optimization of outpatient services.